Meta-methodological aspects of meta-theory of everyday life - Karivets, Ihor (Skhid, 2014)
Nowadays there are a lot of theories of the everyday life in philosophy. The exploration of everyday life has a long tradition from Edmund Husserl and Martin Heidegger to Michel de Certeau and Bernhard Waldenfels. The most of those theories are based on subject-object relation, i.e. researcher-everyday life relation. Such relation is intentional, and researcher is an initiator of intentions which connect his/her with everyday life. Intentions are simply the directedness of the researcher's consciousness towards everyday life as an object of exploration. The author argues that all methods of exploration of everyday life, for example, transcendental and existential, based on the intentional relation between a researcher and everyday life, are false and don't help to understand the nature of everyday life. The other approach to exploration of everyday life is based on the non-intentional relation between a researcher and everyday life and such an approach requires other method, which is meta-method. Such meta-method may be named consciousness of consciousness of everyday life. Consciousness of consciousness of everyday life helps to cognize everyday life as real unity (non-intentional) of object and subject, when a researcher can be aware how clich?s, schemes, habits, customs, etc. are produced. The meta-theory of everyday life based on the consciousness of consciousness of everyday life is free from objectivism and subjectivism of old theories.